2014
DOI: 10.2147/ceor.s59568
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of orbital atherectomy plus balloon angioplasty vs balloon angioplasty alone in subjects with calcified femoropopliteal lesions

Abstract: IntroductionAs cost considerations become increasingly critical when selecting optimal endovascular treatment strategies, a cost-benefit analysis was conducted comparing the Diamondback 360°® Orbital Atherectomy System (OAS) (Cardiovascular Systems, Inc., St Paul, MN, USA) and balloon angioplasty (BA) vs BA alone for treatment of calcified femoropopliteal lesions.Patients and methodsThe clinical outcomes from COMPLIANCE 360°, a prospective, multicenter, randomized study comparing OAS+BA vs BA alone for treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…These results agree with a previous study conducted by Slovacek et al, which found that the utility value was 0.70 to 0.76 in stage IIa-IIb compared with 0.56 and 0.61 in stage III and IV patients, respectively and Weinstock et al found the utility values of patients with PAD during claudication and limb ischemia to be 0.71 and 0.47, respectively [23][24] . The results showed that with increasing age and a serious stage of PAD in accordance with the Fontaine classification, quality of life declined because PAD was a chronic disorder characterized by exertional limb pain, loss of limb, and a high mortality rate.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with a previous study conducted by Slovacek et al, which found that the utility value was 0.70 to 0.76 in stage IIa-IIb compared with 0.56 and 0.61 in stage III and IV patients, respectively and Weinstock et al found the utility values of patients with PAD during claudication and limb ischemia to be 0.71 and 0.47, respectively [23][24] . The results showed that with increasing age and a serious stage of PAD in accordance with the Fontaine classification, quality of life declined because PAD was a chronic disorder characterized by exertional limb pain, loss of limb, and a high mortality rate.…”
Section: Discussionsupporting
confidence: 92%